ANALISIS KEBUTUHAN FASILITAS UTAMA DAN PENDUKUNG PADA JALUR PEDESTRIAN DALAM KAWASAN TOD (STUDI KASUS TOD ISTORA SENAYAN) - Mardiyah Sulistiorini; Lita Sari Baru (Jurnal Ilmiah Global Education, 2023)
The condition of DKI Jakarta as one of the economic centers in Indonesia, has a very high level of population mobility both from within and other cities around it. The application of urban management in the form of Transit Oriented Development (TOD)-based development planning which accommodates the need for human mobilization in the area on foot is one of the principles of organizing a compact city towards a sustainable city. Considering this explanation, this study aims to examine the needs of the main and supporting facilities on the pedestrian path in the TOD area. The method implemented in this study is the collection of literature and secondary data and field verification by comparing the existing conditions in the area with the stipulation of policies that have been approved for further processing in order to provide recommendations for input or improvement in accordance with applicable regulations.